Positive and Negative Ambivalence of Trust to the Teacher Between Students with Different Styles of Pedagogical Leadership - Dorofeev V.A.; Mochalova Y.A. (Психолого-педагогические исследования, 2018)
The model of two types of ambivalence of student’s confidence in the teacher is presented - positive and negative. Integration of psychological parameter ("psychological health" of the subject of the trust) determined by features of a ratio of trust/mistrust and a formalized (construct of the measurement of ambivalence) determined by method of measurement and statistical technology of the analysis of data is the basis for differentiation. In longitudinal analysis and taking into account the contradictoriness of the trust object as the determinant of ambivalence, an empirical verification of the validity of the model was carried out on the sample of students (N = 78) and teachers (N = 4). The statistically significant prevalence of students with a negative ambivalence of confidence in a controversial (liberal) style compared to a consecutive (authoritarian) one is established. A decrease (statistically reliable in the liberal style) of the proportion of such students as the time of interaction with teachers has been increased. The empirical results are interpreted substantively.